2022
DOI: 10.2166/ws.2022.429
|View full text |Cite
|
Sign up to set email alerts
|

Development of a soil wetting pattern estimation model for drip irrigation

Abstract: Accurately estimating the soil wetting pattern that closely reflects the measured value can improve the water use efficiency for drip irrigation. Ignoring the effect of the initial soil water content on the soil wetting pattern affects the accuracy of the estimated results to a certain extent. This research aimed to develop a soil wetting pattern estimation model for drip irrigation that included four easily measurable parameters (i.e., initial soil water content, saturated hydraulic conductivity, total volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Li et al [41] indicated that soil-wetting patterns significantly affect the spatial structure of cotton root under mulched drip irrigation. Li et al [54] found that the larger the emitter discharge rate, the shallower the wetting soil body, and the migration rate and time of the wetting front fit the power function. Small-flow drip-irrigation treatment has achieved higher yield in this experiment, which may be related to the shape of the wetting body and plant roots: (1) Under the same soil type and the same irrigation quota, when the drip emitter is small, the drip irrigation forms a deep, narrow wetting body [55].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [41] indicated that soil-wetting patterns significantly affect the spatial structure of cotton root under mulched drip irrigation. Li et al [54] found that the larger the emitter discharge rate, the shallower the wetting soil body, and the migration rate and time of the wetting front fit the power function. Small-flow drip-irrigation treatment has achieved higher yield in this experiment, which may be related to the shape of the wetting body and plant roots: (1) Under the same soil type and the same irrigation quota, when the drip emitter is small, the drip irrigation forms a deep, narrow wetting body [55].…”
Section: Discussionmentioning
confidence: 99%
“…Drip flow rate is considered one of the most important parameters in the system design and management and can significantly affect the irrigation efficiency. With the same irrigation amount, a smaller drip flow rate has greater vertical depth of the soil wetted zone than a higher drip flow rate, and a larger drip flow rate results in a wide and shallow wetted zone [21,22]. Zhang et al reported that a drip flow rate of 1.38 L/h had 59% and 32% less soil matric potential than that of 2.0 and 3.0 L/h at a shallow soil depth (10-40 cm) and 56% and 20% higher soil matric potential than that of 2.0 and 3.0 L/h at a deep soil depth (70 cm), respectively [23].…”
Section: Effects Of Various Drip Tape Layouts and Drip Emitter Flow R...mentioning
confidence: 99%